The chromogranin A1‐373 fragment reveals how a single change in the protein sequence exerts strong cardioregulatory effects by engaging neuropilin‐1. (1st November 2020) - Rocca, Carmine; Grande, Fedora; Granieri, Maria Concetta; Colombo, Barbara; De Bartolo, Anna; Giordano, Francesca; Rago, Vittoria; Amodio, Nicola; Tota, Bruno; Cerra, Maria Carmela; Rizzuti, Bruno; Corti, Angelo; et al.
Abstract: Aim: Chromogranin A (CgA), a 439‐residue long protein, is an important cardiovascular regulator and a precursor of various bioactive fragments. Under stressful/pathological conditions, CgA cleavage generates the CgA1‐373 proangiogenic fragment. The present work investigated the possibility that human CgA1‐373 influences the mammalian cardiac performance, evaluating the role of its C‐terminal sequence. Methods: Haemodynamic assessment was performed on an ex vivo Langendorff rat heart model, while mechanistic studies were performed using perfused hearts, H9c2 cardiomyocytes and in silico. Results: On the ex vivo heart, CgA1‐373 elicited direct dose‐dependent negative inotropism and vasodilation, while CgA1‐372, a fragment lacking the C‐terminal R373 residue, was ineffective. Antibodies against the PGPQLR373 C‐terminal sequence abrogated the CgA1‐373 ‐dependent cardiac and coronary modulation. Ex vivo studies showed that CgA1‐373 ‐dependent effects were mediated by endothelium, neuropilin‐1 (NRP1) receptor, Akt/NO/Erk1, 2 pathways, nitric oxide (NO) production and S‐nitrosylation. In vitro experiments on H9c2 cardiomyocytes indicated that CgA1‐373 also induced eNOS activation directly on the cardiomyocyte component by NRP1 targeting and NO involvement and provided beneficial action against isoproterenol‐induced hypertrophy, by reducing the increase in cell surface area and brain natriuretic peptide (BNP) release. Molecular docking and all‐atom molecular dynamics simulations strongly supported the hypothesis that the C‐terminal R373 residue of CgA1‐373 directly interacts with NRP1. Conclusion: These results suggest that CgA1‐373 is a new cardioregulatory hormone and that the removal of R373 represents a critical switch for turning "off" its cardioregulatory activity.